The Motives to Borrow - Fatas, Antonio (IMF Working Papers; Working Paper ;, 2019)
Governments issue debt for good and bad reasons. While the good reasons-intertemporal tax-smoothing, fiscal stimulus, and asset management-can explain some of the increases in public debt in recent years, they cannot account for all of the observed changes. Bad reasons for borrowing are driven by political failures associated with intergenerational transfers, strategic manipulation, and common pool problems. These political failures are a major cause of overborrowing though budgetary institutions and fiscal rules can play a role in mitigating governments' tendencies to overborrow. While it is difficult to establish a clear causal link from high public debt to low output growth, it is likely that some countries pay a price-in terms of lower growth and greater output volatility-for excessive debt accumulation.